Incidence of Cancer after a Second Unprovoked Venous Thromboembolic Event - Rézig, Shéhérazade; Mao, Raphael Le; Couturaud, Francis; Lacut, Karine; Delluc, Aurélien (Thrombosis and Haemostasis, 2019)
Patients with two unprovoked venous thromboembolism (VTE) events could be at high risk for cancer diagnosis and may therefore benefit from extended cancer screening strategies. However, accurate data on the incidence of cancer in this population is lacking. In a prospective cohort study, we followed-up with all patients who experienced two unprovoked symptomatic VTE events that occurred in less than 2 years apart. We estimated the 1-year incidence rate of cancer following the second unprovoked VTE event using the Kaplan–Meier method. Potential predictors for cancer diagnosis were assessed using a Cox proportional hazard regression model. Between May 2000 and December 2013, we included 197 patients with two episodes of symptomatic unprovoked VTE that occurred in less than 2 years apart. Their mean age was 66.2 ± 16.3 years, and 122 (51.8%) were male. Seventeen patients were diagnosed with cancer during the year following the second episode of unprovoked VTE, corresponding to a cumulative incidence rate of 9.19% (95% confidence interval [CI]: 5.81–14.37). The 1-year cumulative incidence rate of cancer was 35.88% (95% CI: 19.75–59.25) in patients with VTE recurrence on anticoagulation, 5.51% (95% CI: 2.9–10.32) among patients with a second episode of unprovoked VTE occurring after stopping anticoagulation and 1.15% (95% CI: 0.16–7.88) when time elapsed between the first and recurrent VTE was > 1 year. Our study suggests that the incidence of cancer in patients with a second episode of unprovoked VTE that occurs off anticoagulation, or > 1 year after the first event, is similar to that of patients with a first unprovoked VTE event.
Keywords: unprovoked venous thromboembolism; occult cancer; symptomatic VTE events